2020
DOI: 10.1016/j.buildenv.2020.106994
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic metrics of natural ventilation cooling effectiveness for interactive modeling

Abstract: The evaluation of natural ventilation potential for cooling indoor spaces during the early design phases is of great interest to researchers and practitioners. Among various definitions and usages for natural ventilation potential (NVP) in early design evaluation, this paper reviews and identifies the key performance indicators, and proposes two new dynamic metrics-natural ventilation cooling effectiveness (NVCE) and climate potential utilization ratio (CPUR). The metrics 1 are dynamically responsive to variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Building uncertainties arise mainly from the possible variation of material properties and approximation of physical processes in the building simulation. Nari Yoon [34] proposes two new metrics (NV cooling effectiveness and climate potential utilization ratio) for dynamic response to various design options in both steady and transient states, allowing consideration of thermal mass. Cristina Baglivo studied how envelope design optimization impacts a building's thermal behavior in a certain warm climate [35].…”
Section: General Uncertainties Added and Uncertainty Propagationmentioning
confidence: 99%
“…Building uncertainties arise mainly from the possible variation of material properties and approximation of physical processes in the building simulation. Nari Yoon [34] proposes two new metrics (NV cooling effectiveness and climate potential utilization ratio) for dynamic response to various design options in both steady and transient states, allowing consideration of thermal mass. Cristina Baglivo studied how envelope design optimization impacts a building's thermal behavior in a certain warm climate [35].…”
Section: General Uncertainties Added and Uncertainty Propagationmentioning
confidence: 99%
“…• The air temperature and the average radiant temperature are the two parameters used for evaluating the thermal conditions. The combination of these two temperatures gives the operative temperature, which is calculated from equation (8).…”
Section: Simulation Codesmentioning
confidence: 99%
“…7 However, understanding a climate's potential for natural ventilation should be the first step. A comprehensive review of natural ventilation metrics was presented by Yoon et al 8 The three leading performance indices identified by the authors are the Climatic Potential for Natural Ventilation (CPNV), the Natural Ventilation Cooling Effectiveness (NVCE) and the Climate Potential Utilization Ratio (CPUR). This study also demonstrated the applicability of these measures in a design procedure:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NVCP was used as one of the indicators for assessing ventilation potential. This indicator is based on air temperature and relative humidity (Yoon, Norford, Malkawi, Samuelson, & Piette, 2020).. It is defined as the number of hours within a stipulated time range.…”
Section: Urban Settlement Natural Ventilation Potential Assessmentmentioning
confidence: 99%